Biofortification of common bean as a complementary approach to addressing zinc deficiency in South Africans. (3rd October 2018) - Moloto, Rebahlotse Mapula; Moremi, Lesiba Harry; Soundy, Puffy; Maseko, Sipho Thulane
ABSTRACT: Deficiencies of vitamin A, iodine, iron and zinc (Zn) in humans are caused partly by the consumption of food that has insufficient quantities of these. Their deficiency has a negative impact on the health, wellbeing, social and economic status of human beings. A national survey conducted in 2012 identified deficiencies of vitamin A, Fe, and Zn among other nutrients in South Africans and regarded the deficiencies of vitamin A and Fe as a moderate but not Zn. This review discusses causes of Zn prevalence in low-income South Africans and that it is largely caused by the low content of Zn in their diets. Initiatives to reduce Zn deficiency include fortification of wheat products and maize meal which has failed to address it successfully. Weaknesses of fortification include high cost of fortified food products to low-income populations, poor regulation in ensuring compliance in fortification, non-fortification of sorghum meal, and leaching of fortified nutrients during processing. This review suggests Zn-biofortification of locally-preferred common bean cultivars as an alternative strategy to compliment fortification. The review also discusses advantages of adopting biofortified Nutritional Andean common beans. Furthermore, the review suggests initiatives including evaluation of the common bean genotypes' adaptation to different agro-ecologies.